TESL trainee teachers' perceptions towards the influence of social network on the student's choice of vocabulary in second language writing / Ahmad Firdaus Ahmad Nasri - Ahmad Nasri, Ahmad Firdaus (Faculty of Education, 2014)
The study was conducted to identify the TESL trainee teachers' perceptions towards the influence of social network on the student's choice of vocabulary in second language writing. It was intended to find out if the trainee teachers are aware of social network influence on their students in writing and what do the trainee teachers think about this situation. A number of 68 TESL students who had undergone their teaching practicum from the Faculty of Education UiTM Shah Alam were chosen as respondents. A questionnaire was used in the process of collecting data. The questionnaire included questions that ask about the trainee teacher's awareness towards social network's influence on the student's writing and their perception towards this situation. The findings suggested that the respondents are aware of these influences and effects on their students' second language writing. However, the effects are beyond their control due to the high usage of social network language among the students.